Hubungan Motivasi Kerja dengan Kinerja Guru SMP Negeri 3 Suruh - Fikri Syahnakri Annan; Umbu Tagela; Yustinus Windrawanto (Universitas Muria Kudus, 2023)
This study aims to determine the significance of the relationship between work motivation and teacher performance at SMP Negeri 3 Suruh, Semarang Regency. The type used in this research is correlational research. The sampling technique used in this research is technique total sampling Â by taking as many as 30 teachers according to the population. The data in this study were taken using a scale technique with 4 alternative answers. The data obtained will then be analyzed using correlation techniques kendallâ€™s tau-b with the help of programs IBM Statistics SPSS 25. The results showed that a correlation coefficient of 0.587** was obtained and a significance value of 0.000 (<0.01). These results indicate that there is a significant relationship between work motivation and teacher performance at SMP Negeri 3 Suruh, Semarang Regency.